Fragile ecology rehabilitating former dumpsites back into the community - Guinto , Markus Gabriel J. (College of Architecture, University of the Philippines Diliman, 2022)
Open dumping is among the simplest and most popular methods of solid waste disposal in the world. However, it is also the most damaging as it operates without a careful management of the solid waste itself as well as its byproducts, namely leachates and landfill gasses, which all threaten to harm human communities and the natural environment. The Philippines has banned the creation and operation of open dumpsites in favor of the more systematic sanitary landfills; however, the rehabilitation of these existing former open dumpsites in the country is arguably still in its infancy with slow and incomplete progress towards mitigating the risks that these open dumpsites entail. With that, it is imperative that these former open dumpsites must be overseen and rehabilitated to prevent the further endangerment of both human life and natural environment. As such, this project aims to review the current developments in landfill rehabilitation to see which may be applied in the former Pulang Lupa CDF in Las Pinas City to help lessen and mitigate the hazards it posses towards its surroundings as an example. The project also aims to explore the potentials in converting the available area into a more functional and environmentally-friendly setting that may also be utilized by its neighboring community as a mix of commercial, communal and green spaces through architectural intervention and design.